AI-GENERATED CONCEPT ART IN FILM AND GAMING EDUCATION - Jadhav, Netaji Maruti; Gupta, Anand Kumar; Sharma, Nittin; Garg, Prateek; Divakaran, Prakash; Praveena K N (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The fast development of artificial intelligence (AI) has changed the creative fields, especially film and game education, as AI concept art is starting to redefine the way images are developed. This paper examines the role of AI technology, including Generative Adversarial Networks (GANs) and Diffusion Models, in the development of concept art, the optimization of the creative process, and the increase in the creative potential of students. GANs can create new visual concepts using vast collections of existent pieces of art, which makes it possible to create original landscapes, characters, and environments. Diffusion Models, conversely, enhance the quality of images by solving male noises in iterative steps providing photorealism in imagery, which can be used in film and game design classes as a way of previsualization. The AI approaches implemented in the curricula will enable students to create and develop ideas quickly, experiment with their aesthetics, and learn about the connection between technology and creativity. In addition to technical proficiencies, students gain critical sensitivity with regards to ethical and aesthetic aspects of AI-generated content that includes originality, authorship, and bias. The use of AI-based art generation can help the educators to promote interdisciplinary learning uniting the spheres of design, storytelling, and computer science. In the end, AI-generated concept art will fill in the divide between conventional artistic presentation and computational creativity by providing future levels of filmmakers and game creators with the capability to cooperate successfully with clever machines. Such synergy improves artistic creativity and productivity remaking the borders of visual education in digital age.